School Principal Leadership Management, Motivation, And Work Climate On Teacher Performance Taman 3 State Smp - Dewi, Nuning Nurna; Ardianto, Bambang (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2024)
This research aims to investigate and assess the influence of school principal management, motivation, and working environment conditions on teachers' performance at SMP Negeri 3 Taman. This study employs a quantitative approach by collecting data through distributing questionnaires to teachers. The research sample is drawn from the entire population of teachers at SMP Negeri 3 Taman. Data analysis involves simple linear regression and multiple linear regression tests to evaluate the impact of school principal management, motivation, and working environment on teachers' performance. These findings underscore the importance of the school principal's role in creating a conducive work environment and motivating improved teacher performance. Moreover, the research highlights the importance of motivation and positive working environments in enhancing overall teacher performance. The implications of this research emphasize the need for greater focus on school management, providing adequate motivation for teachers, and enhancing a conducive working environment as a comfortable place for learning and work.